Analysis of Dairy Supply Chain Practices and Their Impact on Food Loss in Banyumas Regency, Indonesia - Nurfaizi, Naufal Ghani; Romadlon, Fauzan (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractFood loss in the dairy supply chain is a challenge that impacts the production efficiency and sustainability of the livestock industry. This study aimed to analyze the effect of supply chain practices, including milking, inventory, transportation, and communication, on food loss in the dairy supply chain in Banyumas Regency, Indonesia. This study used a quantitative approach with multiple linear regression analysis based on data from 46 dairy farmers. The results showed that only transportation significantly affected food loss with a regression coefficient of -0.450 and a p value of 0.004. Poor road infrastructure, inefficient transportation, and inadequate delivery support equipment contributed to milk loss during distribution. Although milking, inventory, and communication did not show significant effects, these practices are still important in maintaining milk quality. Farmers are advised to improve milking hygiene, improve storage systems, and strengthen stakeholder coordination. The implications of this study indicate that reducing food loss can improve milk production efficiency, maintain supply stability, and support farmer welfare. Further studies are recommended to expand the research scope to cooperatives and processing industries to obtain a more comprehensive picture of the dairy supply chain.Keywords: Banyumas Regency, distribution efficiency, food loss, milk supply chain, transportation AbstrakFood loss dalam rantai pasok susu merupakan tantangan yang berdampak pada efisiensi produksi dan keberlanjutan industri peternakan. Penelitian ini bertujuan menganalisis pengaruh praktik rantai pasok, yang mencakup pemerahan, persediaan, transportasi, dan komunikasi, terhadap food loss dalam rantai pasok susu di Kabupaten Banyumas, Indonesia. Studi ini menggunakan pendekatan kuantitatif dengan analisis regresi linier berganda berdasarkan data dari 46 peternak sapi perah. Hasil penelitian menunjukkan bahwa hanya transportasi yang berpengaruh signifikan terhadap food loss dengan koefisien regresi -0,450 dan p value 0,004. Infrastruktur jalan yang buruk, ketidakefisienan alat transportasi, dan alat pendukung pengiriman yang kurang berkontribusi terhadap kehilangan susu selama distribusi. Meskipun pemerahan, persediaan, dan komunikasi tidak menunjukkan pengaruh signifikan, praktik-praktik ini tetap penting dalam menjaga kualitas susu. Peternak disarankan meningkatkan kebersihan pemerahan, memperbaiki sistem penyimpanan, dan memperkuat koordinasi antar pemangku kepentingan. Implikasi penelitian ini menunjukkan bahwa pengurangan food loss dapat meningkatkan efisiensi produksi susu, menjaga stabilitas pasokan, dan mendukung kesejahteraan peternak. Studi lanjutan disarankan untuk memperluas cakupan penelitian hingga ke koperasi dan industri pengolahan guna mendapatkan gambaran lebih menyeluruh tentang rantai pasok susu.Kata kunci: efisiensi distribusi, food loss, Kabupaten Banyumas, rantai pasok susu, transportasi